Predicting support for community corrections: Crime type and severity, and offender, observer, and victim characteristics - Levy, Inna (Punishment & society, 2022)
The aim of the current research was to examine the contribution of crime type and severity as well as offender, observer, and victim characteristics to prediction of perception of community correction (CC) as an appropriate punishment. We conducted a telephone survey among Israeli citizens. A random and representative sample of 573 respondents, aged 20 to 74, evaluated the seriousness of crime scenarios and the appropriateness of CC for each scenario. In different versions of crime scenarios, we manipulated offence type as well as offender and victim characteristics. The results of a logistic regression indicate that perceived lower crime severity, a crime that is not murder, older offender age, and being a secular observer are related with an increased likelihood of supporting community corrections. The discussion addresses these findings in the context of punitive goals (e.g., revenge, retribution), public perception of offender dangerousness, and social identity theory.